(untitled) (International journal of artificial intelligence, 2025)
This article is devoted to the use of fruit names in Uzbek and Turkish folk proverbs. It analyzes the symbols expressed by fruits, their spiritual and cultural significance, and the outlook of the two peoples. This analysis is important in studying the cultural similarities and differences between the two nations.